Think about it! : primary : activities for teaching basic thinking skills - Forte, Imogene ([Nashville] : Incentive Publications, 1981)
1. Imagination 2. Creation (Literary , artistics , etc.)
Faculty
Keywords: Kindergarten -- Methods and manuals; Thought and thinking -- Study and teaching; Educational games